A Survey on Smart City Crime Awareness - Khan, AP; Patil, GS; Chaudhari, R; Patil, NP (International Journal of Computer Sciences and Engineering, 2025)
Present day, cities are not restricted to only constructions and physical infrastructures. They are embracing knowledge based system extending from sensor networks to public databases. Big data is a very valuable resource to make cities extra advanced, intellectual, and unified. Cities are responsible for maintaining a safe and secure place for the public. Big data and technologies are revolutionizing how cities can locate, mitigate and prevent safety issues. This Project involves design and implementation of an application based interface for the Crime Dataset of the city. The application will help public as well as researchers to find safe and habitable locations in development of Smart cities.